SOME COMMENTS ON HISTORICAL RECONSTRUCTION (Scientific journal of the Fergana State University, 2023)
The problem of historical reconstruction is of great importance in the study of the history of ancient period, in modern science there are different approaches and views on this issue. Based on the results of archaeological research and comparative analysis of written sources, it is possible to reconstruct the ancient past. The article deals with the problem of historical reconstruction in archeology, approaches to the restoration of ancient history based on the analysis of existing scientific research.